Studi Kimia Tumbuhan Obat Tradisional Indonesia (1) ELUSIDASI STRUKTUR KIMIA TUMBUHAN "SONGA", Strychnos ligustrida BI. (Loganiaceae) - Partomuan Simanjuntak; Titik K. Prana (Jurnal Kimia Terapan Indonesia, 1998)
The plant of Strychnos species were known as a resource of alkaloid compounds. One of them close to Strychnos ligustrida Bl. which its local name known as "Songa" was collected from Nusa Tenggara Barat, Bima area, and evaluated for their chemical constituents.Results of chemical studies on this plant constituents indicated that two out of several components, colobrine N-oxide and strychnine N-oxide alkaloids have been succesfully isolated and identified.Determination of chemical structure of the alkaloid was conducted by analyzing their spectra of infrared, Nuclear magnetic resonances (one and two) dimensional NMR such as IH-IH COSY, 13C-1H COSY, COLOC and mass spectrometry.